2009
DOI: 10.1016/j.crvi.2009.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The genetic diversity of three peculiar populations descending from the slave trade: Gm study of Noir Marron from French Guiana

Abstract: The Noir Marron communities are the direct descendants of African slaves brought to the Guianas during the four centuries (16th to 19th) of the Atlantic slave trade. Among them, three major ethnic groups have been studied: the Aluku, the Ndjuka and the Saramaka. Their history led them to share close relationships with Europeans and Amerindians, as largely documented in their cultural records. The study of Gm polymorphisms of immunoglobulins may help to estimate the amount of gene flow linked to these cultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 51 publications
3
16
0
Order By: Relevance
“…This is confirmed by two studies of Brucato et al in 2009 and. The Gm polymorphism of immunoglobulins in the Noir Marron sample shows a high African gene contribution (95.7%) and very low European (2.6%) and Amerindian (1.7%) contributions (Brucato et al, 2009). Moreover, the mitochondrial DNA profile of this population is closer to that of Africans than to those of most other African Americans with 99.3% of the haplotypes being of African origin i.e., belonging to haplogroup L lineages.…”
Section: Specific Characteristics Of the 3 Subsets Of Patientssupporting
confidence: 87%
See 1 more Smart Citation
“…This is confirmed by two studies of Brucato et al in 2009 and. The Gm polymorphism of immunoglobulins in the Noir Marron sample shows a high African gene contribution (95.7%) and very low European (2.6%) and Amerindian (1.7%) contributions (Brucato et al, 2009). Moreover, the mitochondrial DNA profile of this population is closer to that of Africans than to those of most other African Americans with 99.3% of the haplotypes being of African origin i.e., belonging to haplogroup L lineages.…”
Section: Specific Characteristics Of the 3 Subsets Of Patientssupporting
confidence: 87%
“…The high frequency of individuals homozygous for the Benin haplotype and for (TA)7 among Noir Marron is consistent with the genetic homogeneity of this population and the extent to which the African genetic contribution has been preserved. This is confirmed by two studies of Brucato et al in 2009 and. The Gm polymorphism of immunoglobulins in the Noir Marron sample shows a high African gene contribution (95.7%) and very low European (2.6%) and Amerindian (1.7%) contributions (Brucato et al, 2009).…”
Section: Specific Characteristics Of the 3 Subsets Of Patientssupporting
confidence: 76%
“…Concerning the Noir Marron population, a preliminary anthropological study on the Gm allotypic system showed a high degree of conservation of the African genetic contribution (95.1%) and very low levels of European (2.6%) and Amerindian (1.7%) contributions. This contradicts expectations based on their cultural exchanges and emphasises the importance of the maroon identity which has shaped their profile of admixture [7]. Moreover, this seems to constitute an original genetic characteristic in comparison with other African American populations inhabiting Latin America.…”
Section: Introductionmentioning
confidence: 89%
“…GM allotypes are located in immunoglobulin constant heavy G chain (IGHG) chromosome 14q32. 3, and have been the most extensively studied, due to their remarkable polymorphism and linkage disequilibrium. On the other hand, KM locus (2p11.2) has only three allotypes [KM (1), KM(2) and KM (3)] encoded by alleles KM*1, KM*2, and KM*3, respectively [1].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to genomic DNA markers discovery and development, the GM system proved to be an essential complement for those anthropological studies aimed at the reconstruction of population history [2][3][4][5]. Some GM haplotypes show particular geographical variation patterns, especially in human populations characterized by a deeply rooted ethnicity [6][7][8][9][10][11][12], and this has made the GM system appropriate to detect admixture and gene flow scenarios [13,14].…”
Section: Introductionmentioning
confidence: 99%